Hydrological and Hydrochemical Characteristics of the Iron-Manganese Meromictic Freshwater Lake Svetloe (Arkhangelsk Region) - Natalia M. Kokryatskaya; Artem V. Chupakov; Kseniya V. Titova; Anna А. Chupakova; Svetlana A. Zabelina; Olga Yu. Moreva; Natalia V. Neverova; Tatyana A. Zhibareva (Journal of Siberian Federal University. Biology, 2018)
Meromictic lakes are a unique model for the study of the anaerobic processes of organic matter degradation, such as methanogenesis and sulphate reduction. As a result of activity of sulfate-reducing bacteria hydrogen sulfide accumulates in monimolimnion of these lakes, whereas chemocline is the area of sharp vertical gradients of physical and chemical conditions and as a consequence is the ecological niche for different planktonic microorganisms. This paper describes some characteristics of meromictic freshwater Lake Svetloe, located in the north of the Arkhangelsk region, for which iron-manganese type of meromixia was defined. The distribution of the studied parameters corresponds to the distribution of the specific for meromictic lakes water layers formed in the presence of stable stratification. In the transition layer (chemocline) a sharp decrease in the oxygen content (almost to the analytical zero) is accompanied by an equally sharp increase in the value of the water conductivity and the emergence of dissolved hydrogen sulfide in the water. In the anaerobic zone the conductivity values remain high and accumulation of nutrients, iron, manganese, and hydrogen sulphide (average 30 mg/l) occurs. Besides, the significant decrease in the content of dissolved sulphate caused by its consumption by sulfate-reducing bacteria was noted in this layer. The number of sulphate-reducing bacteria in the water column during the time of observation varied in the range of 10 – 106 cells/ml with the highest content in the chemocline zone, where the maximum amounts of hydrogen sulphide (up to 130 mg/l) were also found